28 Provision of dietary education in UK-based cardiac rehabilitation: a cross-sectional survey. (20th December 2022) - O'Doherty, Alasdair F; James, Emily; Nichols, Simon; Goodall, Stuart; Butler, Tom
Abstract : Background: The cardioprotective diet is effective in reducing risk of mortality and morbidity in patients with heart disease. Therefore, high-quality dietary education in UK cardiac rehabilitation (CR) is needed. However, little is known about its provision in UK CR. Aim: Understand dietary education provision in UK-based CR: (1) Who delivers it? (2) How is it delivered? and (3) What does it include? Methods: A voluntary, electronic survey (Online Surveys, Jisc, UK) was disseminated in conjunction with the BACPR, between July and October 2021. Providers of dietary education in UK-based CR were eligible to participate. Survey questions related to the profession and qualifications of education providers, and the resources used, content and delivery method of dietary education sessions. Results: There were 49 eligible responses from CR centres, delivering early CR (77.6%), maintenance CR (6.1%) or both (16.3%). Dietary educators included; dietitians (55.1%), specialist nurses (65.3%), and exercise professionals (16.3%). 46.9% of educators had no formal nutrition-related qualifications. A median of two (Range, 1 to 12) diet sessions was provided per CR programme. Most had a cardioprotective diet focus. Resources include British Heart Foundation booklets (93.9%) and the Eatwell Guide (69.4%). Diet history assessment methods varied between centres, with one fifth performing no assessment at the start of the programme; citing lack of time (70.0%), staff (20.0%) or knowledge (30.0%). Frequently, no specific amount of carbohydrate (75.5%), fat (63.3%) or protein (75.5%) was recommended. Comorbidities were used to tailor individual advice or referred to a specialist (figure 1). 87.3% of centres followed up whether advice was implemented by patients. Conclusion: CR programmes consistently include key components of a cardioprotective diet and account for known risk factors in dietary advice. However, many failed to assess diet at baseline. Increased training of practitioners, and time allocated to dietary education in CR, programmes is needed.